Evaluating the effectiveness of ‘MCQ development workshop using cognitive model framework —a pre-post study - Rahila Ali; Amber Shamim Sultan; Nida Zahid (Journal of the Pakistan Medical Association, 2020)
Abstract A workshop on MCQ development using cognitive model framework was conducted for health educators from Aga Khan University (AKU) and other academic institutions. The aim was to develop the skill of preparing MCQs for assessing higher cognitive levels. A pre-post study was conducted, participant satisfaction was evaluated and pre–post test scores were used to assess learning capability of the workshop participants. Out of the 19 who attended the workshop, 16 participated in the pre- and post-tests and were included in the study through convenience sampling. The total duration of the study was six months. There was a significant difference in the overall pre-post test scores of the participants with a mean difference of -4.176 ± 4.83 (p value < 0.05). Continuous....